3D structural modeling of HIV-1 protein (protease) - Liu, Xinyi. (2011)
The human genome itself operates like a factory. Our body is made up of DNAs, RNAs and mostly proteins. Proteins are vital for our survival, and provide various functions in the human living cells. The way a protein functions is determined strictly by its structure, which is formed by a sequence of amino acid residues. But with constant exposure to various diseases and virus, mutations of the protein may occur; which some may be disastrous to the human body. Hence, it is important to model protein structure to aid in better understanding how it functions.